2012
DOI: 10.1080/00380768.2012.733925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of root-zone temperature and N, P, and K supplies on nutrient uptake of cucumber (Cucumis sativusL.) seedlings in hydroponics

Abstract: The nutrient uptake and allocation of cucumber (Cucumis sativus L.) seedlings at different root-zone temperatures (RZT) and different concentrations of nitrogen (N), phosphorus (P), and potassium (K) nutrients were examined. Plants were grown in a nutrient solution for 30 d at two root-zone temperatures (a diurnally Fuctuating ambient 10 C-RZT and a constant 20 C-RZT) with the aerial parts of the plants maintained at ambient temperature (10 C-30 C). Based on a Hoagland nutrient solution, seven N, P, and K nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 44 publications
(44 reference statements)
9
68
0
Order By: Relevance
“…Similar trend was noticed in our study in respect of shoot and root calcium uptake which was positively influenced by cooled RZTs with significant (p < 0.05) differences. Yan et al (2012) demonstrated that more nutrients are accumulated in roots and less is transported to shoots at 10 0 C-RZT as compared to those at 20 ÂșC-RZT, which are similar to our observations. James et al (2008) demonstrated that uptake of all mineral elements was significantly different with each temperature treatment except for B, Fe, and Mo which did not respond to temperature.…”
Section: Nutrients Concentration and Uptake In Shoot And Rootsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar trend was noticed in our study in respect of shoot and root calcium uptake which was positively influenced by cooled RZTs with significant (p < 0.05) differences. Yan et al (2012) demonstrated that more nutrients are accumulated in roots and less is transported to shoots at 10 0 C-RZT as compared to those at 20 ÂșC-RZT, which are similar to our observations. James et al (2008) demonstrated that uptake of all mineral elements was significantly different with each temperature treatment except for B, Fe, and Mo which did not respond to temperature.…”
Section: Nutrients Concentration and Uptake In Shoot And Rootsupporting
confidence: 91%
“…The higher nutrient distribution ratio in shoots at 20 ÂșC-RZT resulted in increased stem growth and higher shoots nutrients concentrations (Lahti et al, 2005). Yan et al (2012) found that differences in nutrient uptake were existed between species as affected by RZT such as increasing solution temperature at 14 ÂșC and 20 ÂșC in cucumbers which showed an increased NO 3 uptake with no effect on phosphate uptake as compared to unheated treatment. Urrestarazu et al (2008) reported that increasing nutrient solution temperature to 18-22 ÂșC increased phosphate uptake in two substrates in cucumber.…”
Section: Nutrients Concentration and Uptake In Shoot And Rootmentioning
confidence: 94%
“…The temperature variation was probably influenced by the variation of the solar radiation, which at the end of the cycle was higher for the winter season. As commented by Yan et al (2012), in optimal temperatures the transpiration rate rises and consequently reduces growth and mass accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted with sweet pepper submitted to different nutritive solutions in hydroponic systems, Dodd et al (2000) observed that the crop growth is accelerated in temperatures of 20°C, when compared to 30°C. Yan et al (2012) related that the specific absorption rates for plant nutrients depends on the root system temperature, and even a little increase in temperature can promote big changes on plant growth and nutrients absorption, affecting the yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation